School-to-work transition of young individuals : what can the ELET and NEET indicators tell us? - Flisi, Sara [Verfasser]; Goglio, Valentina [Verfasser]; Meroni, Elena Claudia [Verfasser]; Vera-Toscano, Esperanza [Verfasser] (Publications Office of the European Union, 2015)
"Early school leavers (ELET), normally face greater difficulties in successfully integrating in the labour market, earn less, have higher unemployment rates, and are more at risk of social exclusion and poverty than those who complete higher levels of education. This can have negative consequences not only at the individual level, but also for the society they live in. While youth unemployment has received wide attention by both researchers and policy makers, especially in some EU countries, it is also important to be aware of the fact that these young ELET are also probably more at risk of becoming inactive instead of unemployed (even more than their adult counterparts). These inactive individuals are potentially quite a disadvantaged group in terms of labour market integration and social commitment. Thus, it is worth paying attention to an indicator of 'joblessness' which accounts for all those who are neither in employment, nor in education or training (NEET), as a more accurate proxy of the size of the group of individuals most at risk on the labour market. Thus, the main objectives of this technical brief are: 1) To provide some descriptive evidence on the size of ELET and NEETs across EU Member States using aggregate data from the Labour Force Survey (LFS); 2) To further examine how countries compare with respect to school-to-work transitions of early leavers from education and training; and 3) To investigate the link between educational attainment and NEET status." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 1.2.2.4 Arbeitslosigkeit; P 2.1 Schulabgänger; I 2.2 Europa; Berufseinmündung; Jugendarbeitslosigkeit; Jugendlicher ohne Schulabschluss; Schulabbrecher; Jugendlicher ohne Ausbildungsvertrag; Indikatoren; Monitoring; Europa